2013
DOI: 10.1590/s1516-05722013000300002
|View full text |Cite
|
Sign up to set email alerts
|

Rendimento e composição do óleo essencial de patchouli (Pogostemon cablin) conforme o tempo de extração

Abstract: O patchouli possui óleo essencial nas folhas com utilização principalmente na indústria de perfumaria. O objetivo foi avaliar o melhor tempo de extração de óleo essencial de folhas secas de patchouli. Os tratamentos foram 1, 2, 3, 4, 5, 6, 7 e 8 horas de extração, através do método de hidrodestilação, com aparelho graduado do tipo Clevenger e balões com capacidade de 2 L.O delineamento foi inteiramente casualizado com três repetições. O material destilado foi seco à sombra até atingir aproximadamente 20% de um… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
(20 reference statements)
1
5
0
2
Order By: Relevance
“…Kumar showed that soaking of dried leaves prior to hydrodistillation led to a 5% (after 12 hr of soaking) to 10% (after 24 hr of soaking) higher yield of PEO . Recently Costa et al reported that an 8 hr hydrodistillation of dried leaves in a Clevenger apparatus statistically did not yield more oil than a 1 hr distillation even though at first glance the percentages of 4.8 (8 hr) and 3.3 (1 hr) suggest otherwise . As their conclusion differs significantly from all others over the past century, it should be treated with some reservation.…”
Section: Influence Of Fertilisation Harvesting Time Drying Fermentmentioning
confidence: 94%
See 1 more Smart Citation
“…Kumar showed that soaking of dried leaves prior to hydrodistillation led to a 5% (after 12 hr of soaking) to 10% (after 24 hr of soaking) higher yield of PEO . Recently Costa et al reported that an 8 hr hydrodistillation of dried leaves in a Clevenger apparatus statistically did not yield more oil than a 1 hr distillation even though at first glance the percentages of 4.8 (8 hr) and 3.3 (1 hr) suggest otherwise . As their conclusion differs significantly from all others over the past century, it should be treated with some reservation.…”
Section: Influence Of Fertilisation Harvesting Time Drying Fermentmentioning
confidence: 94%
“…The average oil percentage in “dried” P. cablin leaves as reported in 72 references was calculated as 2.6% (ranges: 0.54 – 5.2%) . However in view of the discussion below, this figure is not precise as it is dependent on the exact plant material used (cultivar, age, soil and growth conditions), percentage of stems as well as foreign materials (soil, other plant species like weeds), drying and/or fermentation, storage, final percentage of water and the distillation technique, conditions and duration.…”
Section: Influence Of Fertilisation Harvesting Time Drying Fermentmentioning
confidence: 99%
“…Rohloff et al (2005) also observed that the drying process has little influence on the oil peppermint (Mentha x piperita L.), which allow the elimination of the drying process, thus reducing costs for obtaining the essential oil. Increasing the moisture content leads to the opposite effect by reducing the safrole content, possibly due to the maintenance of volatile compounds in the essential oil (Smith and Kassim 1979;Braga et al 2005;Costa et al 2013). This effect is probably due to the maximum gene expression in the fresh biomass and the reduced the variability of individuals in dry biomass, since there was no standardization of plant material by the drying process.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, previous studies have demonstrated the greater effect of EO when compared to their major compounds separately. Essential oils of cinnamon, geranium and thyme showed greater growth-inhibition effect on bacteria such as E. coli and S. aureus than their major compound, linalool (Dorman & Deans, 2000;Chang et al, 2001), alone. The EO used in this stage (Maria Bonita) contains a high concentration of linalool, which is a monoterpene alcohol of high value in the cosmetics market, in addition to being used as a flavoring agent by the food and perfumery industries.…”
Section: Boletín Latinoamericano Y Del Caribe De Plantas Medicinales Y Aromáticas/ 266mentioning
confidence: 92%